2013
DOI: 10.5812/jjm.4864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fungal Allergens in Respiratory Allergic Patients in Ahvaz City, Southwest Iran

Abstract: Background: Fungi are ubiquitous in our environment and they are one of the important causes of allergic diseases. Identification of the most common aeroallergens to which patients are sensitized in a specific area is important in the diagnosis and treatment of allergic rhinitis. Objectives: The purpose of this study was to determine the prevalence of skin reactivity to common fungal allergens and total IgE in patients with allergic rhinitis in Ahvaz city. Patients and Methods:In this cross sectional study, 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
9
2
Order By: Relevance
“…Our results more or less agree with two studies, one was done on allergic conjunctivitis patients and revealed that 66% had positive family history of atopy 13 and another one on allergic rhinitis in which 64.4% of patients had positive family history of allergic disease 14 . Our study revealed slight predominance of male patients (53.1%) which is lower than that reported by Nagrale and coworkers 15 (82.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Our results more or less agree with two studies, one was done on allergic conjunctivitis patients and revealed that 66% had positive family history of atopy 13 and another one on allergic rhinitis in which 64.4% of patients had positive family history of allergic disease 14 . Our study revealed slight predominance of male patients (53.1%) which is lower than that reported by Nagrale and coworkers 15 (82.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have reported contradictory results for positive allergen test in patients based on age and gender which some of them were consistent with results of our study and some others were contrast with our results. In study of Shakurnia et al (2013), the most frequent positive cases were observed at age ranges of 15-35 years old and in male gender (15), although in the present study the most prevalent positive cases were at age range of 46-55 years old and in female gender, the results of the mentioned study were not consistent with results of our study. Kashef and coworkers (2003) showed with evaluation of aeroallergens that the most prevalent positive cases were between individuals older than 15 years old (16), that these results were consistent with our results, there are various reasons reported in results for this difference such as sample size of evaluation, epidemiologic conditions, the rate of exposure of patients, type and size of polyposis.…”
Section: Discussioncontrasting
confidence: 99%
“…The most identified allergens were Plane tree 23 (29.9%) Kochia 22 (28.6%(، Alternaria alternaria 20 (26%) and Pigweed 20 (26%), in contrast none of the Goose, Ambrosia, Artemisia, Hen, Duck and Xanthium allergens were detected in the patients. The most positive cases among the weed were Kochia، Pigweed and Russian thistle whereas Assarehzadegan et al have reported Russian thistle as the most common allergen among weed category (15,17). The sample size also the allergen detection methods which have been used in the studies can be reason for the discrepancies; Prick test in previous studies and specific concentration of IgE in the current study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…AR is characterized by paroxysms of sneezing, rhinorrhea, and nasal obstruction, often accompanied by itching of the eyes, nose, and palate (5). AR is an upper respiratory disease caused by immunoglobulin E (IgE) interference following contact with allergens (6).…”
Section: Introductionmentioning
confidence: 99%